Earnings announcement promotions: A Yahoo Finance field experiment - Lawrence, Alastair; Ryans, James; Sun, Estelle; Laptev, Nikolay (Journal of Accounting and Economics, 2018)
This study presents a field experiment in which media articles for a random sample of firms with earnings announcements are promoted to a one percent subset of Yahoo Finance users. Promoted firms have higher abnormal returns and some evidence of lower bid-ask spreads on the day of the earnings announcement. These results are more pronounced for less visible firms, negative earnings news, and on days with fewer promoted firms. These findings suggest that investor attention affects the pricing of earnings and that retail investors buy stocks that catch their attention, in a setting where attention is randomly assigned.